Uji Kinerja Fotodegradasi Kain Terlapisi Komposit Nanosized Chitosan/TiO2 Terhadap Zat Warna Rhodamine B - Eli Rohaeti; Endang Widjajanti Laksono FX; Anna Rakhmawati (Jurnal Kimia Valensi, 2016)
The coating of nanosized Chitosan/TiO2 composit on cotton fabrics substrate and its performance for dye of Rhodamine B was studied. Nanosized Chitosan/TiO2 composit coated on cotton fabrics was done by dip-coating method through pad-dry-cure technic. Cotton fabric thats was coated by nanosized Chitosan/TiO2 composit was characterized by SEM, XRD, and FTIR. Photodegradation Performance test of cotton fabric coated Nanosized Chitosan/TiO2 composit for dye of Rhodamine B was done under UV ray and sun ray.  It was concluded that was cotton fabric coated nanosized Chitosan/TiO2 can decompose dye of Rhodamine B with UV ray more effective than sun ray. Keywords : Dip-coating, photodegradation, nanosized chitosan/TiO2, cotton fabric, rhodamine B DOI: http://dx.doi.org/10.15408/jkv.v2i1.3083